(untitled) (Academia Journal of Medicine, 2019)
Background: Idiopathic primary glomerular diseases include a group of disorders characterized by pathologic alterations in normal glomerular structure and function, independent of systemic disease processes. Inflammatory cytokines, including MCP-1 and IL-6, plays an important role in glomerular inflammation. In this study we determined whether the measurement of urinary MCP-1 and IL-6 might be useful in assessing the role of these urinary marker in idiopathic primary glomerulonephritis and its relationship with histopathological finding. We found in result the minimum level of MCP-1 and IL-6 was 5.6pg/ml and 7.69pg/ml and the maximum level of MCP-1 and IL-6 was 23.6pg/ml and 60.04pg/ml respectively. The mean and standard deviation were higher in nephrotic range proteinuria than nonnephrotic proteinria. Correlation of urinary MCP-1 and IL-6 with 24 hour urinary protein <3.5gm and ≥3.5gm were analysed. The correlation between urinary IL-6 and histopathological finding of idiopathic primary glomerular diseases were found statiscally significant (p value <0.05). In conclusion, we found that level of urinary MCP-1 was raised in patients with increase degree of interstitial fibrosis and tubulointerstitial infiltrates and urinary IL-6 was noted in high level increase with increase degree of glomerlosclerosis, interstitial fibrosis and tublar atrophy.